COMMUNITY EMPOWERMENT THROUGH RESIK APIK WASTE BANKS IN SRONDOL KULON DISTRICT - Briliani, Rengganis Elok; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
Community empowerment through the Resik Apik Waste Bank is an effort made by the people of Brigif, Srondol Kulon Village, Banyumanik District to utilize household waste into useful items that can increase people's income and keep the environment clean and healthy. This research aims to analyze community empowerment through the Resik Apik Waste Bank in Srondol Kulon Village as well as the inhibiting and supporting factors. The data sources in this research were obtained from interviews, observations and documentation. The informant selection technique was carried out using purposive sampling and accidental sampling. The data sources in this research were obtained from interviews, observations and documentation. The informant selection technique was carried out using purposive sampling and accidental sampling. This research uses the dimensions of empowerment success theory. The results obtained, aspects of access and participation have been fulfilled and support the implementation of empowerment. Dimensions that do not support empowerment, control and well-being. Control in the form of monitoring and assistance is not carried out by the supervisory team, which in this case is the sub-district office. In the welfare dimension, the people of Brigif, Srondol Kulon Village, Banyumanik District still have not experienced a significant increase in income and have not experienced easy access to education and health facilities. Factors inhibiting empowerment are limited managerial abilities and the absence of the ability to manage the market. The driving factor for empowerment is natural resources. Suggestions that can be given are the need for an approach between management and the community, control from the government is needed, increasing the intensity of Resik Apik Waste Bank activities more intensely, program innovation that improves community welfare, internal coordination to create clear communication, identifying opportunities and conducting research on competitors so that consumers can be interested in the products being sold.